A global introduction to Baptist churches - Johnson, Robert E. (New York : Cambridge University Press, 2010)
"This work offers insight into the diversity, breadth, and complexity of the cultural influences that shaped Baptist identity"--
"Coinciding with the four-hundredth anniversary of the birth of the Baptist movement, this book explores and assesses the cultural sources of Baptist beliefs and practices. Although the movement has been embraced, enriched, and revised by numerous cultural heritages, the Baptist movement has focused on a small group of Anglo exiles in Amersterdam in constructing its history and identity. Robert E. Johnson seeks to recapture the varied cultural and theological sources of Baptist tradition and to give voice to the diverse global elements of the movement that have previously been excluded or marginalized. With an international communion of over 110 million persons in more than 225,000 congregations, Baptists constitute the world's largest aggregate of evangelical Protestants. This work offers insight into the diversity, breadth, and complexity of the cultural influences that continue to shape Baptist identity today"--
Introduction; Part I. Foundations: 1. The primal shaping processes of the global Baptist movement; Part II. Age of Emerging Baptist Denominational Traditions, 1600-1792: 2. Seeds for diversity amid an early Anglo prevalence; Part III. The Frontier Age, 1792-1890: 3. Baptists' frontier age in the british empire; 4. Baptists' frontier age in the United States; 5. Baptists' frontier age in Europe, Africa, Asia, and Latin America; Part IV. The Age of Proliferating Traditioning Sources, 1890-Present: 6. Baptists' evolving traditioning sources in Africa, Asia, and Oceania; 7. Baptists' evolving traditioning sources in Latin America, the Caribbean, Europe, and Eurasia; 8. Baptists' evolving traditioning sources in North America; Part V. Beliefs and Practices: 9. Baptists' beliefs and practices.
No series statement on cloth binding.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Baptists; RELIGION / Christianity / Baptist; Electronic books